Preparation and Properties of Magnetically Responsive Graphene/Boron Nitride/Iron Oxide Filler Composite Epoxy Resin Materials - Yiheng Yu; Duo Zhang; Hui He; Chaogui Luo; Ming Zhou (Nanomaterials)
In this paper, magnetically responsive graphene/boron nitride/iron oxide fillers were prepared by growing iron oxide on the surface of graphene/boron nitride fillers via liquid-phase reaction. By adding the composite filler into the epoxy resin and utilising magnetic field-assisted curing, the composites were prepared to effectively improve the thermal conductivity of the composites while maintaining the insulating properties. The thermal conductivity of the composite filler is 2.1 Wm−1K−1, and the volume resistance is 4.63 × 1012 Ω·cm when the mass ratio of the composite filler is 25%, and the thermal stability and ablation resistance of the composites are improved compared with that of the pure epoxy resin.